Assessment of genotype-by-environment interactions of white quality protein maize hybrids in Bangladesh (Bangladesh Journal of Agricultural Research, 2017)
Present study assessed genotypes and their interactions with environments (GEI) for plant height, days to maturity and grain yield of 40 maize hybrids including two local checks across five different locations of Bangladesh. Thirty eight white QPM (Quality Protein Maize) hybrids were collected from CIMMYT, Mexico. The AMMI (additive main effect and multiplicative interactions) and GGE (genotype + genotype × environment) model were used to assess the additive and multiplicative effects of the interactions. Significant variations were found for genotypes (G), environments (E) and GEI for all the studied characters. The environment of Gazipur is poor while those of Ishurdi and Rangpur are rich for QPM hybrids production. Considering three parameters viz., mean, bi and S2di, it was evident that all the genotypes showed different responses of adaptability under different environmental conditions. Among the hybrids E21, E23, E30 and E22 exhibited bi~1 and S2di~0 for all the characters under study, which clearly indicated that the hybrids are stable across the environments. The hybrids E11, E25, E37 and E4 had bi value significantly different from the unity with non significant S2di value for one or more characters studied, indicating high responsiveness of the hybrid but suitable for favorable environments only. E5 was a good yielder and stable over environments. Considering the yield potentiality and stability parameters five hybrids were found promising over the locationsBangladesh J. Agril. Res. 42(2): 259-271, June 2017